Optimization of optical and mechanical properties of real architecture for 3-dimensional tissue equivalents: Towards treatment of limbal epithelial stem cell deficiency - Massie, Isobel (Acta Biomater, 2015)
Limbal epithelial stem cell (LESC) deficiency can cause blindness. Transplantation of cultured human limbal epithelial cells (hLE) on human amniotic membrane (HAM) can restore vision but clinical graft manufacture can be unreliable. We have developed a reliable and robust tissue equivalent (TE) alternative to HAM, Real Architecture for 3D Tissue (RAFT). Here, we aimed to optimize the optical and mechanical properties of RAFT TE for treatment of LESC deficiency in clinical application. The RAFT TE protocol is tunable; varying collagen concentration and volume produces differing RAFT TEs. These were compared with HAM samples taken from locations proximal and distal to the placental disc. Outcomes assessed were transparency, thickness, light transmission, tensile strength, ease of handling, degradation rates and suitability as substrate for hLE culture. Proximal HAM samples were thicker and stronger with poorer optical properties than distal HAM samples. RAFT TEs produced using higher amounts of collagen were thicker and stronger with poorer optical properties than those produced using lower amounts of collagen. The ‘optimal’ RAFT TE was thin, transparent but still handleable and was produced using 0.6 ml of 3 mg/ml collagen. Degradation rates of the ‘optimal’ RAFT TE and HAM were similar. hLE achieved confluency on ‘optimal’ RAFT TEs at comparable rates to HAM and cells expressed high levels of putative stem cell marker p63α. These findings support the use of RAFT TE for hLE transplantation towards treatment of LESC deficiency.